2010
DOI: 10.1088/0004-637x/714/1/680
|View full text |Cite
|
Sign up to set email alerts
|

PHYSICAL PROPERTIES OF DENSE CORES IN THE Ρ OPHIUCHI MAIN CLOUD AND a SIGNIFICANT ROLE OF EXTERNAL PRESSURES IN CLUSTERED STAR FORMATION

Abstract: Using the archive data of the H 13 CO + (J = 1-0) line emission taken with the Nobeyama 45 m radio telescope with a spatial resolution of ∼ 0.01 pc, we have identified 68 dense cores in the central dense region of the ρ Ophiuchi main cloud. The H 13 CO + data also indicate that the fractional abundance of H 13 CO + relative to H 2 is roughly inversely proportional to the square root of the H 2 column density with a mean of 1.72 × 10 −11 . The mean radius, FWHM line width, and LTE mass of the identified cores a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
69
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 93 publications
(210 reference statements)
14
69
1
1
Order By: Relevance
“…This is equivalent to Pext /kb ≈ 1.8 × 10 7 K cm −3 , an order of magnitude higher pressure than that found by Maruta et al (2010), but similar to the total pressure in Ophiuchus P/kb ∼ 2 × 10 7 K cm −3 estimated by Johnstone et al (2000).…”
Section: External Gas Pressuresupporting
confidence: 78%
“…This is equivalent to Pext /kb ≈ 1.8 × 10 7 K cm −3 , an order of magnitude higher pressure than that found by Maruta et al (2010), but similar to the total pressure in Ophiuchus P/kb ∼ 2 × 10 7 K cm −3 estimated by Johnstone et al (2000).…”
Section: External Gas Pressuresupporting
confidence: 78%
“…This is equivalent to P ext /k b ≈ 1.8 × 10 7 K cm −3 , an order of magnitude higher pressure than that found by Maruta et al (2010), but similar to the total pressure in Ophiuchus P/k b ∼ 2 × 10 7 K cm −3 estimated by Johnstone et al (2000).…”
Section: External Gas Pressuresupporting
confidence: 80%
“…Maruta et al (2010) estimate a typical surface pressure on cores in Ophiuchus of P ext /k b ≈ 3 × 10 6 K cm −2 , sufficient to influence the energy balance of the cores. Similarly, Johnstone et al (2000) estimate core surface pressures P ext /k b ∼ 10 6−7 K cm −3 by treating the starless cores they identify in Ophiuchus as pressure-confined Bonnor-Ebert spheres.…”
Section: External Gas Pressurementioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies of starless cores suggested that external gas pressure might be instrumental in confining dense cores in at least some cases (Maruta et al 2010;Pattle et al 2015). We apply the method used by Pattle et al (2015) to estimate the external pressure on starless cores in the Ophiuchus molecular cloud to our sample of starless cores.…”
Section: Energy Balance and Stabilitymentioning
confidence: 99%